Sistem Pendukung Keputusan Seleksi Penerimaan Atlet Pusat Pendidikan dan Latihan Pelajar (PPLP) Dengan Menggunakan Metode Smarter - Eliyah Sari Sipayung; Bister Purba (STMIK Budi Darma, 2020)
An athlete must have good knowledge, skills, personality and discipline in following the coaching or the ongoing race or competition. The problem in the selection of athletes for the Student Education and Training Center (PPLP) is that they are not objective enough. The decision-making technique in the SMARTER (Simple Multi-Attribute Rating Technique Exploiting Ranks) method is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important it is compared to other criteria. It is hoped that to overcome this, a decision support system for the selection of athletes in the Student Education and Training Center (PPLP) will be built using the Smarter method at the Office of Youth and Sports (DISPORA) North Sumatra Province which will be designed using Visual Basic 2008 and using Microsoft Access 2007. The Visual Basic design will produce a calculation and ranking process.Keywords: Decision Support System, Athlete, Smarter.